Short-term low-temperature glow discharge nitriding of 316L austenitic steel - T. Frączek; M. Olejnik; J. Jasiñski; Z. Skuza (Metalurgija, 2011)
The AISI 316L austenitic steel after glow discharge nitriding at temperature of T = 673 K and duration of τ=14,4 ks, for two different variants of specimen arrangement in the glow-discharge chamber was investigated. In order to assess the effectiveness of nitriding process, the surface layers profile analysis examination, surface hardness and hardness profile examination, the analysis of surface layer structures and corrosion resistance tests were performed. It has been found that application of a booster screen effects in a nitrogen diffusion depth increment into the 316L austenitic steel surface, what results in the surface layer thickness escalation.